The Strategic Aspects of Functional Position Development in Diy Local Government - Hadilinatih, Bening (Journal of World Science, 2024)
Developing competence and distributing human resources within the state civil apparatus (ASN) is crucial for enhancing their professionalism. This study aimed to identify constraints and alternative strategies for developing competence in functional positions within the Yogyakarta Special Region Government (DIY). Using a qualitative descriptive analysis, the research highlighted several obstacles in functional position development, including limited training types, budget constraints, scheduling conflicts, and insufficient information about available training. Training institutions responsible for developing the competence of functional officials must adhere to legal requirements, particularly those holding accreditation from the relevant Guiding Agency. Collaboration with universities or accredited training institutions is also necessary, particularly in education. Additionally, there is a need to ensure that competent teaching staff are available for specific types of functional training. To address these challenges, the selection of training types must align with a mapped-out understanding of the competency needs of functional officials in the DIY Regional Government. By considering these needs, the government can better target the development of its human resources, ensuring that functional officials receive the appropriate training to fulfill their roles effectively. These steps will help overcome current barriers and support ASN's long-term professionalism and competence in functional roles.